Design of an Auditorium within the Quality University of Berastagi Campus - Sandros Timoti Tambun; Dasrizal; Ferdinand Sinuhaji (Indonesian Journal of Advanced Research, 2026)
This study aims to design the Quality University Berastagi Auditorium Building as a facility capable of supporting various academic and non-academic activities through the application of the Green Architecture concept. The concepts examined include energy efficiency, natural lighting and ventilation, the use of environmentally friendly materials, rainwater management, and room acoustic quality. The method used was qualitative descriptive research through the collection of primary and secondary data, literature review, case studies, site analysis, and space requirements analysis conducted during the design process. The results of the study produced an auditorium design that is functional, comfortable, energy-efficient, adaptable to the climate of Berastagi, and supports sustainable and environmentally conscious campus development.